ChemInform Abstract: The Electrochemical Synthesis of Polycationic Clusters. Issue 13 (March 2016) - Schulz, Christopher; Daniels, Joerg; Bredow, Thomas; Beck, Johannes
Abstract: Electrochemical dissolution of elemental Te in ionic liquids (IL) or in liquid SO2 is studied under dry conditions.